PENERAPAN E-BISNIS DALAM SISTEM TRANSPORTASI UDARA - Minda Mora Purba (JURNAL TEKNOLOGI INDUSTRI, 2015)
In the air transportation system , e -business has a very important role . By using the value chain models formulated Michael Porter , the role of e -business is able to help companies in the main activity and supporting companies . In the main activity , e -business helps companies associated with the operation of airlines, inbound and outbound logistics , marketing , ticket sales companies , and service or service to the consumer . While the support activities , e -business infrastructure to support both physical and information , human resource management (human resources management ) , technology development (technology development ) and procurement activities. Keywords : air transportation system, fully integrated, applications, e-business